Dental discrepancies in black adolescents: evaluating impacts on well-being - Langoski, Jean Érick; Meira, Ana Claudia Lima de Oliveira; Santamaria-Junior, Milton; Menezes, Carolina Carmo de [UNESP]; Meneghim, Marcelo de Castro; Vedovello, Silvia Amélia Scudeler (FapUNIFESP (SciELO), 2025)
The aim of this study was to compare the esthetic, functional, and psychosocial impact of mandibular crowding and maxillary midline diastema in black adolescents. A cross-sectional study was conducted with 420 black (brown and black, distinguished according to Brazilian Institute of Geography and Statistics – IBGE) adolescents aged 12 with normal occlusal relationships. Esthetic (OASIS) and functional/psychosocial (OHIP-14) impact related to the need for orthodontic treatment in groups with mandibular crowding and maxillary midline diastema, and those without these conditions: G1, without crowding and diastema (n 113); G2, without crowding and with diastema (n 67); G3, with crowding and without diastema (n 202); and G4, diastema, and crowding (n 38) were evaluated. Generalized linear models were estimated for the effects of diastema, crowding, and the interaction between them, with a significance level of 5%. There was no significant influence of crowding and diastema on the OHIP-14 (p>0.05). However, the groups with diastema had higher OASIS scores, irrespective of crowding (p<0.05). The maxillary midline diastema influenced the esthetic perception of black adolescents.
Keywords: Adolescent; Esthetics, Dental; Malocclusion; Orthodontics